Analyzing the level of digitalization among the enterprises of the european union member states and their impact on economic growth - Jarosław Brodny; Magdalena Tutak (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The dynamic development of information and communication technology (ICT) reported in recent years has caused significant changes in almost all areas of social and economic life. The digitalization process resulting from this development is now becoming a determinant of both progress and modernity. This issue has been addressed in this paper, and thereby we present a methodology developed to study the level of digitalization and the use of innovative technologies among the enterprises of the EU-27 countries. The research was conducted using selected indicators-determinants (10) characterizing the main digital technologies and infrastructure associated with their implementation in the enterprises under study. Based on these indicators, the Entropy-Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) method was used to determine the index (level) of digitalization among the companies of the EU-27. The level of use of digital technologies and infrastructure for Industry 4.0 was also determined. Another important goal of the study was to determine a relationship between the values of the digitalization index for the EU-27 countries and the economic parameters characterizing their economies. For this analysis, non-parametric tests such as the Kendall's Tau and Spearman's rank correlation coefficients were applied. The results significantly enrich the knowledge of methodology for studying the level of digitalization and its status among the enterprises of the EU-27. These findings provide great opportunities for interpretation and practical application, especially in terms of building an innovative knowledge-based economy. They show great diversity of the EU-27 countries in the field of digitalization and poor results reported in this area by the so-called 'new EU' countries. Among the many interesting findings, it is worth pointing out the positive impact of spending on research and development on the process of digitalization of enterprises. The results should be used when creating a digitalization strategy for individual countries and their groups.
Keywords: 650; digital transformation; Entropy-MOORA method; EU-27; Industry 4.0; open innovation; sensor-based systems